Silver nanoparticles improve growth and protect against oxidative damage in eggplant seedlings under drought stress - Nadiyah M. Alabdallah; Md. Mahadi Hasan; Abdalrhaman M. Salih; S.S. Roushdy; Aisha S. Al-Shammari; Sumayah I. Alsanie; Mohamed El-Zaidy (Plant, Soil and Environment, 2021)
Drought stress is a significant abiotic stressor that has a negative impact on crop production and global food security systems. Drought stress was applied to eggplant seedlings with various field capacities (FC), 80% FC as control, 50% FC, 35% FC, and 20% FC. AgNPs were synthesised from green chemical methods, whereas different concentrations of AgNPs (0, 0.1, 0.2, 0.5 µmol) were applied exogenously on drought-stressed eggplants. Drought stress decreased the growth parameters (plant height, fresh mass, dry mass, leaf area), photosynthetic pigments (Chl a, Chl b, carotenoids), and protein content while increased the proline, hydrogen peroxide (H2O2), malondialdehyde (MDA) content, and activity of the antioxidant enzymes, i.e., superoxide dismutase (SOD) and catalase (CAT). AgNPs restricted proline accumulation and reduced H2O2, MDA content by upregulating the antioxidant enzymes. Overall, the current study's findings indicated that AgNPs are an effective eco-friendly and low-cost application for plant growth under drought stress, with the potential to mitigate the impact of drought on plants.